Neuraminidase Inhibitor of Garcinia atroviridis L. Fruits and Leaves Using Partial Purification and Molecular Characterization - Muchtaridi Muchtaridi; Rina Fajri Nuwarda; Emmy Hainida Khairul Ikram; Aisyah Saad Abdul Rahim; Amirah Mohd Gazzali; Habibah A. Wahab (Molecules, 2022)
Neuraminidase (NA) is an enzyme that prevents virions from aggregating within the host cell and promotes cell-to-cell spread by cleaving glycosidic linkages to sialic acid. The best-known neuraminidase is the viral neuraminidase, which present in the influenza virus. Thus, the development of anti-influenza drugs that inhibit NA has emerged as an important and intriguing approach in the treatment of influenza. Garcinia atroviridis L. (GA) dried fruits (GAF) are used commercially as seasoning and in beverages. The main objective of this study was to identify a new potential neuraminidase inhibitor from GA. A bioassay-guided fractionation method was applied to obtain the bioactive compounds leading to the identification of garcinia acid and naringenin. In an enzyme inhibition study, garcinia acid demonstrated the highest activity when compared to naringenin. Garcinia acid had the highest activity, with an IC50 of 17.34–17.53 µg/mL or 91.22–92.21 µM against Clostridium perfringens-NA, and 56.71–57.85 µg/mL or 298.32–304.31 µM against H1N1-NA. Based on molecular docking results, garcinia acid interacted with the triad arginine residues (Arg118, Arg292, and Arg371) of the viral neuraminidase, implying that this compound has the potential to act as a NA enzyme inhibitor.